Sediment load and suspended sediment concentration prediction - Becvar, M.(Ceske Vysoke Uceni Technicke, Prague (Czech Republic). Katedra Hydromelioraci a Krajinneho Inzenyrstvi) E-mail:martin.becvar@fsv.cvut.cz (Soil and Water Research - UZPI (Czech Republic), 2006)
This paper presents a methodology to predict sediment loads and suspended sediment concentrations (SSC) in large European river basins. It was developed in order to improve sediment modelling in the GREAT-ER point source pollution river modelling package. The basic principle of the methodology is to estimate annual sediment load at the point of interest and the amount of water that transports it. The amount of transported material is then redistributed in the corresponding water volume which determines sediment concentrations. Sediment yields were measured in 44 river basins belonging to major European rivers and the results were compared with the traditional empiric sediment yield estimators. Three approaches for sediment yield prediction were introduced on that basis. The methodology was verified using some data from the Czech Republic. Observed SSC were compared with the predicted ones which validated the methodology for SSC prediction.